4t + 13t + 2 = 17t + 2
If 4t + 5 = 37, then t = 8.
9t = 4t + 120 9t-4t = 4t - 4t + 120 5t = 120 5t/5 = 120/5 t = 24 24 is your answer
4t - 2p
T(t + 4)
T+(3-2t)=4t+1. Assuming the two T's , T and t are the same variable, lets proceed. t+(3-2t)=4t+1 3-t=4t+1 2-t=4t 2=5t last step is yours
7s + 4t
4t2 - 12 = 4*(t2 - 3) which has no further rational factors
(u + 4)(6u - t)
4t-1 = t+2 3t -1 = 2 3t = 3 t = 1
It is an equation and the value of t is 1
6t -2t + 5u = 4t - 5u
4t-523 = -519
3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)
Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals", "squared", "cubed" etc. As it is now, there is no equation, only an expression without any symbol between 34 and 4t.
(3t + 2)(4t - 1)
t + 10 - 4t = -11 Subtract 10 from each side: t - 4t = -21 ie -3t = -21 t = -21/-3 t = 7.
28 t2 - 17 t - 3 = (7t + 1) x (4t - 3)
In the expression 5-4t it is t that is the variable
Size 4 are longer and slimmer than 4T. 4T is cut more for a toddler and allows room for a diaper.